2006
DOI: 10.1177/097265270600500305
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Models for Forecasting Stock Price Index in the Bombay Stock Exchange

Abstract: Artificial Neural Network (ANN) has been shown to be an efficient tool for non-parametric modelling of data in a variety of different contexts where the output is a non-linear function of the inputs. These include business forecasting, credit scoring, bond rating, business failure prediction, medicine, pattern recognition and image processing. A large number of studies have been reported in literature with reference to the use of ANN in modelling stock prices in western countries. However, not much work along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 20 publications
0
20
0
5
Order By: Relevance
“…Ravichandran et al (2005) used a feed-forward back propagation network to predict the stocks trading on the Bombay Stock Exchange (BSE). Dutta et al (2006) used feed-forward ANN models for forecasting the BSE sensitive index (BSE-SENSEX) with reasonable accuracy. Swanson and White (1997) suggested that a single hidden layer feed-forward ANN offers a useful and flexible alternative to fixed specification linear models.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Ravichandran et al (2005) used a feed-forward back propagation network to predict the stocks trading on the Bombay Stock Exchange (BSE). Dutta et al (2006) used feed-forward ANN models for forecasting the BSE sensitive index (BSE-SENSEX) with reasonable accuracy. Swanson and White (1997) suggested that a single hidden layer feed-forward ANN offers a useful and flexible alternative to fixed specification linear models.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…The key element of this paradigm is the novel structure of the information processing system (Haykin, ); that is, how layers of neurons (also called processing elements) are organized and connected. The three essential features of an ANN structure are (1) the basic computing elements, referred to as neurons, (2) the network architecture describing the connections between the neurons and (3) the training algorithm used to find values of the network parameters for performing a particular task (Dutta et al , ). The neurons that receive input represent the input layer, and the neurons that generate the output represent the output layer.…”
Section: Artificial Neural Network Modelling and Literature Reviewmentioning
confidence: 99%
“…However, machine learning algorithms were used by some authors for stock market prediction. While Dutta et al (2006) evidence that ANN performs satisfactorily in predicting closing prices of SENSEX, the leading index of Bombay Stock Exchange, Qin et al (2012) evidence support for Random Forest based trading model for the Singapore exchange. Sala (2011) develops an alternative approach of liquidity risk modelling using a recurrent neural network and shows that machine learning may be an important alternative while modelling liquidity risk.…”
Section: Literature Reviewmentioning
confidence: 99%